New Directions for Online Education Research: What Have We Overlooked? - Nogueira, Bruna (Peer Beyond Graduate Research Conference, 2025)
As online higher education continues to expand, concerns persist around student isolation, attrition, and low interactivity, raising questions about its quality. This study conducts a critical review of online education literature, uncovering overlooked areas. Findings reveal that the lack of meaningful interpersonal relationships remains a key challenge, with learners' subjective experiences largely underexplored. This gap calls for research focused on the subjective aspects of interpersonal relationships in online teaching and learning in higher education contexts.